Revisiting the description of Atractoscion macrolepis (Perciformes: Sciaenidae): Another argument for comprehensive taxonomy - Gouws, Gavin; Kruger, Jerraleigh L.; Smale, Malcolm; Henriques, Romina; Potts, Warren M. (Zootaxa, 2024)
Atractoscion macrolepis was described as a species separate to A. aequidens, distinguished by a geographically-separated distribution, genetic evidence and a diagnostic meristic character: the number of pored lateral line scales. However, the distinction of these species and description of A. macrolepis were based on the examination of a limited number of specimens, some of which were incorrectly catalogued and possibly wrongly identified. Moreover, earlier data, demonstrating the overlap of the supposedly diagnostic character, were overlooked or not considered fully. The present study aimed to reconsider the distinction of these two species and to highlight characters for identification, using a more extensive representation of specimens, additional character sets and multivariate analyses. Seven meristic characters, 24 morphometric measurements and nine otolith variables were examined from up to 33 specimens of A. aequidens and 52 specimens of A. macrolepis. These were compared among the species and subjected to univariate and multivariate analyses, including Principal Component Analyses (PCAs) and Discriminant Function Analyses (DFAs). No meristic characters, including the number of lateral line scales, could distinguish the species, with modes being identical or with nodes differing, but ranges overlapping. While the PCA of size-transformed morphometric data revealed some separation of the two species, the DFA indicated significant and reliable discrimination. Considering the otolith variables, the PCA showed weak separation of the two species, while fair discrimination was observed in the DFA. ANOVAs indicated a number of significant differences for some transformed otolith measurements, but there were no clear trends with respect to proportions that would discriminate the species. Further exploration of those morphometric variables highlighted as contributing to separation in the PCA and DFA provided a number of variables that, when expressed as a proportion of SL and used in combination, discriminate A. aequidens and A. macrolepis: HL, MCL, PFL, AFL and PLFL. The present study does not contest the taxonomic status of A. macrolepis, the distinction of which has been demonstrated repeatedly, but does refute the characters regarded as diagnostic. In light of this, an updated key is provided for the five species of the genus. The study demonstrates the value of increased specimen representation and having data fully available rather than in summary.